Teacher Well-being in Private Schools in Azerbaijan - Hajiyeva, Sabina; Huseynzada, Ulkar; Guluzada, Nargiz (ADA University, 2024)
This study aims to explore teacher’s perception of well-being and the factors contribute teacher well-being in Azerbaijani private schools. Although there has been done research investigating teachers’ well-being, there was no any research investigating especially private school teachers’ well-being and the factors contributing to their well-being. Additionally, unlike previous ones, this research demonstrates qualitative approach to the problem. The study’s target population and sample size consist of 12 private school teachers. For the primary data collection semi-structured interviews were utilized. According to findings, teachers defined their well-being as having enough energy and creativity to do something and their physical, emotional, and social health. The collected data and analysis revealed that collaboration with peers, relationship with parents, students learning, and behavior, administrative support and work-life balance are the factors contribute teachers’ well-being in Azerbaijani private schools. In order to improve teachers’ well-being administration should accept them as a human and show care for them and should create supportive environment where teachers can share their thoughts with each other respectively, parents should be more responsible and listen teachers’ concern for their children, students should be behaving appropriately and show interest for the lesson, and work-life balance should be achieved that teachers have more time for their personal life
Keywords: Teachers--Azerbaijan--Psychology; Teachers--Job satisfaction--Azerbaijan; Private schools--Azerbaijan--Faculty; Work-life balance--Education--Azerbaijan; Teacher-student relationships; School administrators--Azerbaijan; Education